Olistoliths as overlooked sources of information: an example from Pliensbachian belemnites and ammonites of Lukoveček (Czechia, Western Carpathians) - Jan Geist; Robert Weis; Ján Schlögl; Martin Košťák; Martin Mazuch (Swiss Journal of Palaeontology)
Abstract The Lower Jurassic cephalopod fauna recorded from an olistolith in the vicinity of Lukoveček (Czech Republic, Moravia) has been studied in detail. Seven ammonite taxa belonging to four genera and eight belemnite taxa of five genera are herein described and discussed within the stratigraphical and palaeobiogeographical context. Ammonites indicate the Upper Pliensbachian Margaritatus and Spinatum ammonite zones, which is consistent with the stratigraphic ranges of the associated belemnites. The analysis of the cephalopod assemblage recorded in the olistolith shows a relatively low diversity in the Upper Pliensbachian of Western Tethys. Our study suggests possible faunal exchanges between the Central and the Outer Carpathian units, between the European shelf and Western Tethys. This research contributes significant insights into the palaeogeographical development and sedimentary history of the Western Carpathians during the Lower Jurassic period, highlighting the importance of the Lukoveček olistolith as a unique information source of otherwise disappeared palaeogeographical areas.